2012
DOI: 10.1134/s0024490212030066
|View full text |Cite
|
Sign up to set email alerts
|

Strontium isotope composition of the lower proterozoic carbonate concretions: The Zaonega Formation, Southeast Karelia

Abstract: The middle part of the volcanosedimentary Zaonega Formation of the Ludikovian Suprahorizon (approximately 2.0 Ga) includes large carbonates concretions and lenses in shungite layers. Carbonate lenses and concretions are primarily elongated and flattened, and their thickness varies from tens of centimeters to a few meters. Some lenses retain relicts of lamination. Concretions are composed of calcite or dolomite. They contain abundant organic matter, as well as mica, talc, chlorite, quartz, and pyrite crystals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…Additionally, it is unlikely that the oxidation of CH 4 , (e.g., through anaerobic oxidation of methane, AOM) was the sole source of DIC because none of the obtained δ 13 C carb values in calcite-rich carbonates is lower than -17‰. Typical AOM derived carbonates show δ 13 C carb values well below -20‰ (e.g., Campbell, 2006 Kuznetsov et al (2012) for the Zaonega Formation.…”
Section: Fluid Composition and Sourcementioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, it is unlikely that the oxidation of CH 4 , (e.g., through anaerobic oxidation of methane, AOM) was the sole source of DIC because none of the obtained δ 13 C carb values in calcite-rich carbonates is lower than -17‰. Typical AOM derived carbonates show δ 13 C carb values well below -20‰ (e.g., Campbell, 2006 Kuznetsov et al (2012) for the Zaonega Formation.…”
Section: Fluid Composition and Sourcementioning
confidence: 97%
“…This has led to the interpretation that the transition from the 13 C-rich carbonates to those with values near 0‰ in the middle part of the Formation denotes the end of the Lomagundi-Jatuli Event (Melezhik et al, 2015). The 13 C-depleted carbonate rocks in the upper part of the Formation were originally interpreted as concretions (Kuznetsov et al, 2012;Melezhik et al, 1999) but more recent studies have shown that they are variably altered sedimentary layers Melezhik et al, 2015). Interpretations of such low δ 13 C carb values are quite variable and include: incorporation of C derived from anaerobic methane oxidation (Yudovich et al, 1991), diagenetic recrystallisation and incorporation of C derived from oxidised organic matter (Krupenik et al, 2011), and recycling of organic matter involving microbial and/or thermal reduction of sulphates and Fe-and Mn-oxides (Melezhik et al, 2015).…”
Section: Previous Geochemical Studiesmentioning
confidence: 99%
“…As reported by Peryt & Anczkiewicz () based on analyses of Miocene evaporites, substantial inflow of continental waters during brine formation has the potential to shift the Sr‐isotope ratio of marine gypsum and anhydrite towards non‐marine, more radiogenic values. Alternatively, ascending fluids may have been modified by interaction with terrigenous siliciclastics and/or continental crust (Meister et al ., ; Kuznetsov et al ., ). In the Araripe Basin, the concretion‐bearing deposits are superimposed on a heterogeneous lithological succession made up of terrigenous and marginal marine siliciclastics, which cover a complex suite of Proterozoic crystalline basement (Martill, ).…”
Section: Discussionmentioning
confidence: 97%
“…The formation of silico-carbonate "abiotic" nodules by interactions between sediments and microorganisms lead to the formation of the accretion laminae observed in these nodules and in the stromatolites, from the Proterozoic [22][23][24] to modern analogues [25]; and microbially mediated calcification can be traced back for at least the Proterozoic [26][27][28][29][30]. Additionally, these "abiotic" concretions typically develop from a central point and present often a zonal concentric structure; they may contain concentric and lateral accretion laminae [31], characterized by variations in the isotopic and geochemical compositions of the different growth zones [32].…”
Section: Discussionmentioning
confidence: 99%